10(-2)+6n=12

Simple and best practice solution for 10(-2)+6n=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10(-2)+6n=12 equation:


10(-2)+6n=12

We simplify the equation to the form, which is simple to understand
10(-2)+6n=12

Reorder the terms in parentheses
+(-20)+6n=12

Remove unnecessary parentheses
-20+6n=+12

We move all terms containing n to the left and all other terms to the right.
+6n=+12+20

We simplify left and right side of the equation.
+6n=+32

We divide both sides of the equation by 6 to get n.
n=5.3333333333333

See similar equations:

| -1.5x=1.5 | | 6x-4=6(x-6) | | 2+5(5x-6)=122 | | 10x+5y=550 | | .10b+15=.15b+10 | | 9.4=d+56 | | 2(x+14)=6 | | 16x^2-a^2= | | 6(5x+7)-8x=7x-33 | | .10(d)+.25(46-d)=6.70 | | -3(x-7)=-18 | | 7.7w-2.5=43.7 | | -99=-3-3(8-3n) | | 3(5a+2)=2(3a-6) | | 4(x-3)-r+2x=5(3x-7) | | 27c^3+343y^3=0 | | 5x^3-3x^2-35x+21=0 | | 60+80x=160+70x | | 7.8-18=2.6p-5 | | 60x+80x=160+70x | | -.04-(-3)-25.003= | | -165=-3x-3(6+6x) | | x+3x+4x-2+3x-2=169 | | 0.3c+1.4=0.3(c-7) | | 4x+x-5=4x+3 | | 2(x-7)=-3x-(2-6x) | | -6p-3=-12-5p | | (6-4)(8b^2-5b+6)= | | 13-[5+5y-3(y+3)]=-3(4y-7)-[8(y-1)-16y+18] | | 2(b+8)-9=18 | | 3=y-21 | | 8x-3=2x+33 |

Equations solver categories